2023
DOI: 10.58286/27626
|View full text |Cite
|
Sign up to set email alerts
|

Crack mode analysis of cement mortars with signal - based acoustic emission techniques

Abstract: Determining the crack mode in structures made of brittle materials, such as concrete and masonry, is important for structural analysis and failure prediction. Fractures monitored with the acoustic emission technique (AE) are commonly classified into different modes using Rise angle (RA) – Average Frequency (AF) analysis, the simplified Green's functions for moment tensor analysis (SiGMA), and frequency spectrum analysis. However, the classification limits are dependent on the material, the test setup, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The crack mode of the located AE events is investigated using the rise angle (RA), and the average frequency (AF) of the first AE hit in the event. The basis of classification is based on the findings of the author's prior work [49]. The mode of AE events was identified as a tensile mode when the ratio between the AF and RA is above 0.5.…”
Section: Size Of the Fracture Process Zonementioning
confidence: 99%
“…The crack mode of the located AE events is investigated using the rise angle (RA), and the average frequency (AF) of the first AE hit in the event. The basis of classification is based on the findings of the author's prior work [49]. The mode of AE events was identified as a tensile mode when the ratio between the AF and RA is above 0.5.…”
Section: Size Of the Fracture Process Zonementioning
confidence: 99%
“…However, the difficulties in determining the point of crack initiation in experimental setups have led to debate over the validity of the measured tensile strength [10]. Recent research has examined fracture patterns in the Brazilian splitting test, both experimentally and numerically [11,12], and found that the crack initiation point can vary [13]. Some studies have reported that the crack initiates and propagates from the area under the loading points [14], while others have found that it starts at the center of the disc [15].…”
mentioning
confidence: 99%